The Impact of the Reputation of Bio-Life Science and Engineering Doctoral Programs on Regional Economic Development. - Hill, Edward W.; Lendel, Iryna (Economic Development Quarterly, 2007)
Retrospective data on the academic reputation of PhD programs in the biological and life sciences and engineering are used in regression models to measure the influence of academic quality on the growth in employment and in per capita income for metropolitan areas in the United States over the two parts of the recently completed business cycle (1994 to 2000 and 2001 to 2003). The quality of doctoral research programs in science and technology fields was positively associated with growth rates in employment and per capita income in metropolitan areas during the expansion phase of the business cycle. Regions with quality science and technology doctoral programs experienced declines in employment growth rates following the recession. There was an inverse relationship between academic quality and per capita income following the recession, indicating that regional earnings bubbles built up during the expansion. Strong path dependencies are exhibited in the models. Reprinted by permission of the publisher.